Liminal Identities. Portraits of Surviving Domestic Violence - Campos, Susana (Philosophical journal of conflict and violence, 2019)
The paper looks into a participatory art project developed in two women’s refuges, one in Portugal and the other in England. Addressing liminality after surviving violence, the project constructs a portrait of survivors, utilising feminist pragmatist aesthetics to transfer representational agency to participants. Against a background where women who have experienced domestic violence have often been portrayed in simplistic representations of damaged beauty, the study sought to gain a deeper understanding by holding visual art workshops with participants (Portugal, England) and analysing data from verbal testimonies (England). The paper contributes to a discussion of the practical issues negotiated when establishing a representational power balance between researchers and research participants. It does this by providing a critical discussion of three ethical problems emerging in relation to the project. The first concerns the dominant representation of survivors, the second the need for participants’ anonymity and the third the challenges of inequality in qualitative research.